Engendering ethics: recognition and inclusion of intersectional identities in queer communities when conducting population survey research - Andreassen, Kim; Mason, Leanda Denise; Chen, Julian (Taylor and Francis Group, 2024)
This paper delves into the critical importance of ethical considerations in research, with a primary focus on gender, sex, and sexual orientation. Recognizing the vulnerabilities and complexities inherent in these communities, we emphasize here the necessity of ethical awareness throughout all research phases. Ethical obligations may extend to ensuring cultural sensitivity, safety, and equitable resource distribution. The core ethical principles of autonomy, beneficence, non-maleficence, and justice are promoted here to serve as a viable framework for ethical research. These principles require meticulous attention to informed consent, minimizing harm, maximizing benefits, and promoting fairness throughout the research process. The paper delves into the intricacies of queer identities, highlighting the fluidity and intersections among gender, sex, and sexual orientation. Recommendations are proposed to integrate ethical principles seamlessly into research. This paper underscores that ethical considerations are not just a regulatory requirement but a moral obligation, essential for upholding the rights and well-being of all individuals. By embedding ethical principles into research, we can contribute to a more inclusive, equitable, and just society, amplifying the voices and experiences of marginalized communities while minimizing harm and promoting social change.